Implementasi IT Project Management Dalam Pembuatan Sistem Informasi Monitoring Pagu Dan Anggaran (Simpora) - Firdaus, Mohamad (Jurnal Teknologi Informasi (JUTECH), 2022)
SIMPORA according to the Head of Tanjung pandan Customs office Jerry Kurniawan SE, ME stands for (Sistem Informasi Monitoring Pagu dan Anggaran) Ceiling and Budget Monitoring Information System. In making the application using a Project Management approach. Project management is a scientific discipline in terms of planning, organizing, managing, to be able to achieve project goals. More specifically, the Project Management used is SDLC (Software Development Life Cycle with the waterfall method. while project scheduling uses Gantt Chart with the CPM Method (Critical Path Method) as a reminder of the critical time in the project so that it can be a concern for stakeholders in overseeing the course of the project.